Conservation tillage is a sustainable way of vegetable production - Singh, S. K.; Lama, T. D.; Bahadur, Anant; Chaukhande, Paresh; Singh, Raghwendra; Singh, B. (Indian Horticulture, 2019)
Conservation tillage practices like minimum tillage, no-tillage or zero tillage have the potential as an energy use and cost-efficient technology in vegetable production, besides improving soil properties and reducing greenhouse gas emission. Such resource conservation technologies, which are components of conservation agriculture are the key to sustainable farming and will help to meet the challenges of achieving food and nutritional security under declining land and water resources, increasing input costs and threats of climate change.